The Impact of COVID-19 on the Fast-Food Industry in Malaysia - Daisy Mui Hung Kee; Nurul Farhana binti Mohd Nazri; Nurrida binti Misbah; Nurul Asyiqin binti Nazril; Nur Hasmizah binti Musa; Nurizzah Fatihah binti Abdul Hamid (AIBPM Publisher, 2021)
Many businesses worldwide are badly affected due to the COVID-19 outbreak. As the Covid-19 pandemic spreads around the world, business person should create new business methods during this socio-economic, cultural, and health crisis. How to address the future is another critical question for businesses. Although the pandemic has affected businesses in different profound ways due to the various social, cultural, economic, and environmental factors, experience sharing and learning from successful businesses can help policymakers and business leaders to come up with innovative and effective strategies to minimize the adverse impact of the pandemic on the business operation. The study aims to determine how Covid-19 affected the fast food industry in Malaysia. Due to the Movement Control Order (MCO), all Malaysians are required to stay at home. The data of this study was collected through primary data and secondary data. The surveys using online Google form was conducted as primary data to gain more information regarding the topic. There are as many as 100 customers were surveyed. The results showed the fast food industry sustained operations and they adopted digitalization technologies. Digital technologies have influenced fast food restaurant strategies during the global pandemic, while technology may enable digital transformation, fast food restaurants are rapid to match the changes. Digitization opens new possibilities for fast food restaurants to sustain their business. With digital infrastructures in place like mobile devices, Wi-Fi networks, and online payment systems, it brings convenience to both business and customers. Deepening digitization has helped fast food restaurants to become more customer centric.